A giant tonsillolith camouflaging as a peritonsillar abscess - Vijayan, Vikas; Sebastian, Susan K.; Raj, Abhijeet; Amar, Priyanka S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Giant tonsillolith is a rare clinical entity. We present the case of a 7 years old male who presented with sore throat and difficulty in swallowing. Right tonsil was bulging into the oropharynx with marked peritonsillar swelling and inflammation and a provisional diagnosis of peritonsillar abscess was made. Contrast enhanced computed tomography scan revealed a large-sized tonsillolith on the right side. The patient underwent elective stone removal and tonsillectomy.